2015
DOI: 10.1007/s11033-015-3857-y
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the molecular basis of cancer metabolism and the Warburg effect

Abstract: In differentiated normal cells, the conventional route of glucose metabolism involves glycolysis, followed by the citric acid cycle and electron transport chain to generate usable energy in the form of adenosine triphosphate (ATP). This occurs in the presence of oxygen. In hypoxic conditions, normal cells undergo anaerobic glycolysis to yield significantly less energy producing lactate as a product. As first highlighted in the 1920s by Otto Warburg, the metabolism exhibited by tumor cells involves an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…The majority of ATP production in mammalian cells are largely dependent on oxidative phosphorylation and glycolysis (Ngo et al 2015). As our studies and previous reports have shown that doxycycline affected both mitochondrial respiration and glycolysis (Fig.…”
Section: Doxycycline Decreased Atp Levels In Cervical Cancer Cell Linessupporting
confidence: 81%
“…The majority of ATP production in mammalian cells are largely dependent on oxidative phosphorylation and glycolysis (Ngo et al 2015). As our studies and previous reports have shown that doxycycline affected both mitochondrial respiration and glycolysis (Fig.…”
Section: Doxycycline Decreased Atp Levels In Cervical Cancer Cell Linessupporting
confidence: 81%
“…We predict 32% (24/74) of our identified mutations to have biological potential, with roughly half (9/24) present in sufficient frequency (>70%) to alter mitochondrial function. Further biological studies are required to determine the overall impact of these somatic mutations on energy metabolism, specifically their potential to drive tumor respiration from one of oxidative phosphorylation to aerobic glycolysis [29], a common cancer phenomenon known as the Warburg effect [30]. …”
Section: Discussionmentioning
confidence: 99%
“…This is known as the Warburg effect; it is less efficient in terms of ATP generation (2 vs 36 ATPs), but enables glucose to be used as a carbon source for the synthesis of nucleotides, amino acids and lipids for cell growth and division (Ngo et al, 2015). Some viruses can reprogramme cell metabolism to assist virus replication.…”
Section: Cell Respiration Oxygen and Virusesmentioning
confidence: 99%